Un nuevo texto: Manos y Pensamiento: realidades de la interpretación, perspectivas de formación - Lara Guzmán, Gabriel (Lee La LEE, 2023)
Un nuevo texto: Manos y Pensamiento: realidades de la interpretación, perspectivas de formación